2018
DOI: 10.1002/sdtp.12220
|View full text |Cite
|
Sign up to set email alerts
|

70‐4: Higher‐Contrast and Lower‐Haze Transparent Screen Using Waving Cholesteric Liquid Crystals

Abstract: We have successfully developed a lowest haze transparent screen which can display higher contrast images than ever, by aligning waving cholesteric liquid crystals. Because the high contrast image is highly visible even in a bright environment, this could change signage and automotive industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…We found that by changing the surface energy of the substrate, it is possible to control creating a wave alignment of the PCM films, as shown in Fig. (a‐I) . Figure (b) shows photos of PCM films from various directions.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We found that by changing the surface energy of the substrate, it is possible to control creating a wave alignment of the PCM films, as shown in Fig. (a‐I) . Figure (b) shows photos of PCM films from various directions.…”
Section: Resultsmentioning
confidence: 88%
“…3(a-I). 6 Figure 3(b) shows photos of PCM films from various directions. The PCM film with wave alignment exhibits diffuse reflection, and the reflected color can be seen from various directions, as shown in Fig.…”
Section: Control Of Viewing Angle Of Reflected Lightmentioning
confidence: 99%
“…We found that waving alignment is essential to realize both reflection light control and to project real image [2], since simple planar orientation cholesteric liquid crystals act as a mirror, which does not project real image.…”
Section: Concept Of Brightest Rear-type Transparent Screenmentioning
confidence: 99%
“…Cholesteric liquid crystals perform as a diffraction grating when its spiral axis is tilted [5]. Thus, we aimed to make waving aligned [2] tilted cholesteric liquid crystals film to generate diffraction…”
Section: Figure 3 Concept Of Rear-type Transparent Screen Using Cholesteric Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation